Design and Fabrication of a Novel T-Shaped Piezoelectric ZnO Cantilever Sensor - Kai Yang; Zhigang Li; Dapeng Chen (Active and Passive Electronic Components)
A novel T-shaped piezoelectric ZnO cantilever sensor for chem/bio-detection is designed and fabricated with MEMS technology. By using Rayleigh-Ritz method, the fundamental resonant frequency formula of T-shaped cantilevers is deduced for the first time and is validated by simulation results and experimental results. From this formula, we can easily find the superiority of adopting T-shape for the cantilevers. The complete process of the cantilever sensor is then successfully developed. The cantilever sensor is actuated by a layer of high-quality ZnO film with preferred (002) orientation, which is evaluated by SEM and XRD. The key step of the process is protecting the ZnO film from KOH etching by a novel and effective method, which has rarely appeared in the literature. Finally, this cantilever sensor is measured by a network analyzer, and it has a fundamental resonant frequency of 24.60 kHz. The cantilever sensor developed in this study illustrates the feasibility and potential for many miniaturized sensor applications.